The impact of test language on PISA scores. New evidence from Wales - Jerrim, John; López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (Wiley, 2022)
In this paper we investigate the link between thelanguage in which pupils take the Programme forInternational Student Assessment (PISA) test andthe scores they achieve in this assessment, focusingupon the case of Wales. Using five rounds of PISAdata and an instrumental variable approach, we showhow pupils who took the test in Welsh score around0.3 standard deviations (30 PISA test points) lower inreading, mathematics and science than their peerswho took the test in English. This finding is robustto different model specifications and statistical ap-proaches. We argue that this may indicate that theacademic performance of teenagers in Wales maybe underestimated in PISA – particularly amongstthose who take this test in Welsh.
https://openpolicyfinder.jisc.ac.uk/id/publication/5011
Keywords: Rendimiento académico - Gales (Gran Bretaña); Estudiantes - Evaluación; PISA; Wales; Home language; Test language